Understanding regional groundwater flow using water-rock interaction processes and anthropic signatures in a fractured volcanic aquifer - Oliveira, Paula Cristina Neuburger de; Athayde, Gustavo Barbosa; Licht, Otavio Augusto Boni; Gastmans, Didier; Amaral, Bianca do; Tavares, Diego Alberto; Garcia, Lucas Henrique; Athayde, Camila de Vasconcelos Müller (Elsevier, 2023)
This research evaluated the hydrochemistry of a fractured volcanic aquifer at Paraná 3 Basin, in the western region of the state of Paraná, southern Brazil. Geochemical rock data from the literature were used to describe the distinctive characteristics of the principal geological units in the area, Pitanga and Paranapanema Formations, both belonging to the Serra Geral Group. Data from x-ray diffraction were obtained to deepen the study of hydrogeochemical processes. Previous studies did not consider the differences in the lithogeochemistry of the group, in the terms contemplated in this research. In addition, the research also approaches the evaluation of the flow depth contribution in the groundwater chemistry and the analysis of hydrogeochemistry processes. For this analysis, a set of chemical data was utilized on 35 groundwater samples from water supply boreholes at Paraná 3 Basin. From shallow to deep flow, there was an increase in pH, electrical conductivity, total dissolved solids, total alkalinity and a decrease in CO2. These parameters exert the main physical-chemical groundwater controls, which are identified by changes in the major ions along the flow lines, as well as by variations in trace elements. The water-rock interaction becomes increasingly evident in the intermediate and deep flows, standing the higher alkalinity, pH, electrical conductivity, total dissolved solids (TDS) and most of the trace elements at Pitanga Formation. Pitanga Formation presents higher medians of alkalinity (95.5 mg.L-1), electrical conductivity (225 μS.cm-1) and TDS (140.0 mg.L-1) than Paranapanema Formation (57.0 mg.L-1; 130 μS.cm-1 and 90.0 mg.L-1, respectively). Furthermore, the pH distribution shows greater values starting at the 60% percentile in Pitanga Formation (8.24), compared to Paranapanema (8.10). Despite such differences, it was not possible to distinguish the geological units with the hydrochemical characterization, probably because both units are mainly represented by rocks of basic composition, with a similar mineralogical basis. The shallow hydrogeochemical processes are characterized by the weathering of Fe–Mg silicates and plagioclase, changing to a predominance of ion exchange in deeper flows. Calcite precipitation is a secondary process, associated with calcium consumption towards deeper flows. Anthropic influences are mainly observed with more elevated concentrations of NO3-, PO43-, Cl- and K+, occurring in the entire basin, and they are strongly evidenced by the correlation between Cl- and NO3- in most samples.
Keywords: Fractured aquifer; Groundwater flow; Hydrochemistry; Serra Geral Aquifer